PENGARUH PENYULUHAN TERHADAP PERILAKU PENCEGAHAN HIV/AIDSPADA SISWA SMA DI PROVINSI MALUKU - bazrul makatita (STIKES Pasapua Ambon, 2019)
Introduction : Counseling is an educational activity carried out by spreading the message, instilling confidence, where the community is not only aware, knows and understands, but also wants and can make a recommendation that can improve living standards. This study aims to analyze the changes in knowledge, attitudes and actions of senior high school students before and after counseling in the experimental group and control in efforts to prevent transmission of HIV/AIDS in Maluku Province. The study was conducted at Senior high school no 2 of West Seram in Seram Regancy and senior high school no 4 leihitu in Central Maluku Regency. Methode : The method used in this study was Quasi Experiment with data collection techniques using questionnaires distributed to 80 respondents. Technique of collecting Sample using systematic random sampling, the data were analyzed using statistical analysis through tabulation followed by Wilcoxon test. Result :The study for the experimental group after counseling showed that there was an influence of counseling on knowledge, attitudes and actions with significant values p value = 0.000 ˂ 0.05 and the control group in Posttest 1 had no effect with significant values of knowledge p value = 0.083, attitude 0.157, and 0.083 while in Posttest 2 there was a change with a significant value of knowledge p value = 0.001, attitude 0.014 and action 0.003 ˂ 0.05, this is because after posttest 1 the respondent had a desire to know more about HIV/AIDS prevention.